The Influence of Service Quality, Brand Image, and Customer Satisfaction on Customer Loyalty of Bekam Therapy Center Jember - Dwi Purnomo, Deddy; Restu Permana, Anindya; Irawan, Dedy; Qomariah, Nurul (International Journal of Management Science and Information Technology, 2023)
Health is currently an important concern after the outbreak of the Copid 19 Pandemic. Cupping therapy is an alternative for people to maintain their own health from free radical attacks that are currently spreading in the community due to pollution and chemicals. This study aims to examine the effect of service quality, brand image, and customer satisfaction on customer loyalty at Bekam Therapy Center Jember. The sample in this study consisted of 100 customers who had cupping at the Cupping Therapy Center using a nonprobability sampling technique. Tests were carried out using multiple linear regression using the SPSS 25 Software tool. The results of the analysis show that service quality affects customer loyalty, brand image affects customer loyalty and customer satisfaction affects customer loyalty at the Jember "Bekam Therapy Center".